Ion Leakage at Dayside Magnetopause in Case of High and Low Magnetic Shears - Stepanova, M (Blackwell Publishing Ltd, 2017)
The nature of energetic ions in the magnetosheath of the Earth is studied using the data of the Time History of Events and Macroscale Interactions during Substorms mission. Three intervals of the multiple crossings of the magnetopause during northward orientation of the interplanetary magnetic field and quiet geomagnetic conditions were selected to illustrate the behavior of ion distribution functions near the subsolar region in case of high and low magnetic shears. For all analyzed events, the velocity and thickness of the magnetopause was estimated using the simultaneous measurements in two satellites. The ion spectra in the magnetosphere and magnetosheath were fitted by kappa and bi-kappa distributions, respectively. It was found that during high shear events the energetic part of the ion spectra is practically identical inside and outside the magnetopause. On the other side, for low shear events the energetic fluxes of ions in the magnetosheath are lower. We argue that in case of high magnetic shear, the magnetopause becomes transparent when the ion Larmor radii is comparable or larger than the thickness of the magnetopause. It may explain coincidence of the energetic part of spectra inside and outside the magnetosphere. We discuss the reason for the changes of spectra at low magnetic shear. ©2017. American Geophysical Union. All Rights Reserved.